General synthesis method of high-entropy oxide nanosheet and application of high-entropy oxide nanosheet in methane dry reforming

Synthesis of high-entropy oxide nanosheets by solvent-free method solves the problem that traditional methods are difficult to obtain nano-scale particles, and achieves efficient catalysis and long-term stability in methane dry reforming reaction.

CN119911982APending Publication Date: 2025-05-02XI AN JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510094571.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Traditional high-entropy oxide synthesis methods are difficult to obtain nano-scale particles, resulting in limited catalytic performance and complex preparation process.

Method used

The high entropy oxide nanosheets were synthesized by solvent-free method, and the nanosheets were obtained by premixing the hydrated metal nitrate with anhydrous citric acid, and heating them in an oil bath for magnetic stirring, and then calcining them.

Benefits of technology

The obtained high entropy oxide nanosheets exhibit high conversion rate and long-term stability in methane dry reforming reaction, with significantly higher catalytic activity than traditional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119911982A_ABST
    Figure CN119911982A_ABST
Patent Text Reader

Abstract

The invention discloses a general synthesis method of a high-entropy oxide nanosheet and application of the high-entropy oxide nanosheet in methane dry reforming, and the general synthesis method comprises the following steps: 1, mixing a plurality of hydrated metal nitrates and anhydrous citric acid according to a ratio, and manually premixing to obtain a mixture; 2, heating the mixture in an oil bath, and carrying out magnetic stirring until a foamed solid is formed; and 3, placing the foamed solid in a muffle furnace, calcining in air, and removing organic components to obtain the high-entropy oxide nanosheet. The high-entropy oxide nanosheet is synthesized through a simple and effective solvent-free method, and the obtained nanosheet shows excellent catalytic activity and stability in a methane dry reforming reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high entropy oxides, and in particular to a general synthesis method of high entropy oxide nanosheets and application of the same in methane dry reforming. Background Art

[0002] High entropy oxides (HEOs) have become important candidates for the next generation of catalysts due to their unique physical and chemical properties.

[0003] However, traditional HEOs synthesis methods, such as ball milling CN111790397B and sol-gel method CN114530590A, usually result in micron-sized particles that lack effective structural features, have limited specific surface area and poor intrinsic activity, thus limiting their catalytic performance. Therefore, the development of environmentally friendly, simplified preparation process and high quality and functional nanostructured HEOs is the focus of current research. Summary of the invention

[0004] In order to overcome the defects of the above-mentioned prior art, the present invention provides a general synthesis method of high entropy oxide nanosheets and its application in methane dry reforming. High entropy oxide nanosheets are synthesized by a simple and effective solvent-free method, and the obtained nanosheets exhibit excellent catalytic activity and stability in the methane dry reforming reaction.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] A general method for synthesizing high entropy oxide nanosheets comprises the following steps:

[0007] Step 1: premixing a plurality of hydrated metal nitrates and anhydrous citric acid in proportion to obtain a mixture;

[0008] Step 2: heating the mixture in an oil bath and stirring it magnetically until a foamy substance is formed;

[0009] Step 3: placing the foamed solid in a muffle furnace and calcining it in air to obtain high entropy oxide nanosheets after removing organic components.

[0010] In the step 1, the ratio of the hydrated metal nitrate to anhydrous citric acid is 1-2.5 moles of anhydrous citric acid per mole of metal ion.

[0011] In step 1, the hydrated metal nitrate is a mixture of any N elements that meet the solid solution properties among hydrated magnesium nitrate, hydrated cobalt nitrate, hydrated iron nitrate, hydrated nickel nitrate, hydrated aluminum nitrate, hydrated manganese nitrate, hydrated calcium nitrate, hydrated copper nitrate, and hydrated lanthanum nitrate, where N is greater than or equal to 5.

[0012] In the step 2, the heating temperature in the oil bath is 120-150°C.

[0013] In step 3, the calcination is carried out at 500-1000° C. for 3-5 hours. The organic framework after the metal ions and citric acid complex are burned and decomposed at high temperature to generate corresponding metal oxides.

[0014] The high entropy oxide nanosheets obtained in step 3 include but are not limited to the following structures:

[0015] Inverse spinel (Cr 0.2 Mn 0.2 Co 0.2 Ni 0.2 Fe 0.2 )3O4、(Mg 0.4 Fe 0.2 Co 0.2 Ni 0.2 )Al2O4; Perovskite La-(Mn 0.2 Cu 0.2 Co 0.2 Ni 0.2 Fe 0.2 )O3; spinel (Ni 0.2 Mg 0.2 Cu 0.2 Mn 0.2 Co 0.2 )Al2O4; cubic Ni 0.2 Mg 0.2 Cu 0.2 Zn 0.2 Co 0.2 O.

[0016] The high entropy oxide nanosheets prepared by the method are used as catalysts in methane dry reforming reactions.

[0017] Specifically:

[0018] The catalyst is reduced in situ at 700°C for 1-5h with 10% H2 (Ar as the balance gas) before the reaction begins; then the catalyst is added to methane (CH4) and carbon dioxide (CO2) to react and generate synthesis gas, and the reaction is carried out at a temperature of 700-850°C and a reaction pressure of normal pressure;

[0019] When the reaction temperature is 700-850°C, an efficient and stable catalytic effect can be achieved to catalyze the reaction of methane and carbon dioxide to produce synthesis gas.

[0020] The feed gas ratio of CH4:CO2:Ar is 1:1:3 (Ar is the balance gas), and the space velocity GHSV is 30000 mL h -1 gcat -1 .

[0021] The high entropy oxide nanosheets exhibit the following performance in a methane dry reforming reaction: CH4 conversion rate>89%; CO2 conversion rate>92%; and long-term stability of more than 400 hours.

[0022] The method was used to prepare (Mg 0.4 Fe 0.2 Co 0.2 Ni 0.2 )Al2O4 high entropy oxide nanosheets were synthesized by a eutectic solvent-free method, namely (Mg 0.4 Fe 0.2 Co 0.2 Ni 0.2 )Al2O4-co-melt, (Mg 0.4 Fe 0.2 Co 0.2 Ni 0.2 )Al2O4 is spinel type.

[0023] Moreover, it exhibits significantly higher catalytic activity and stability in methane dry reforming reaction than samples prepared by traditional Sol-Gel method.

[0024] (Mg 0.4 Fe 0.2 Co 0.2 Ni 0.2 )Al2O4-co-melt presents a nanosheet structure rich in mesopores;

[0025] (Mg 0.4 Fe 0.2 Co 0.2 Ni 0.2 )The metal elements in Al2O4-co-melt show high entropy characteristics of uniform dispersion. Among them, Fe, Co, and Ni elements can be reduced by H2 to form FeCoNi ternary alloys of uniform size and carried by nanosheets. The FeCoNi ternary alloy improves the electronic structure of Ni, making it more conducive to the adsorption and activation of methane and carbon dioxide.

[0026] The high entropy oxide nanosheets prepared by the method are used as catalysts including but not limited to methane dry reforming reactions.

[0027] In the premixed system of step 1, the role of anhydrous citric acid is to act as a chelating agent. Hydrated metal nitrates usually have a lower melting point and can provide metal ions and carboxyl groups in citric acid for complexation reaction after melting.

[0028] In step 2, under oil bath and magnetic stirring, three carboxyl groups in citric acid react with metal ions to form a network coordination polymer.

[0029] In step 3, calcination will burn and remove organic matter in citric acid, etc., and each metal element will be reintegrated and crystallized to form the corresponding high entropy metal oxide.

[0030] Beneficial effects of the present invention:

[0031] The high entropy oxide nanosheets synthesized in the present invention exhibit higher conversion rate and lower carbon deposition tendency, demonstrating the importance of nanosheet morphology on catalytic performance.

[0032] (Mg 0.4 Fe 0.2 Co 0.2 Ni 0.2 )Al2O4-co-melt presents a mesoporous nanosheet structure. The nanosheet structure increases the effective surface area, thereby improving the catalytic activity. At the same time, the nanosheet structure helps to improve the thermal stability and structural stability of the catalyst, which can effectively prevent the pulverization, sintering and shedding of particles at high temperatures, reduce carbon deposition and extend the life of the catalyst.

[0033] The precipitation of FeCoNi nanoparticles from the matrix enhanced the catalytic activity; the upward shift of the d-band center promoted more efficient charge transfer between adsorbates and significantly improved the catalytic efficiency.

[0034] The (Mg 0.4 Fe 0.2 Co 0.2 Ni 0.2 )Al2O4 nanosheets achieved CH4 conversion >89%, CO2 conversion >92% at 750°C and long-term stability of more than 400 hours. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 For a inverse spinel (Cr 0.2 Mn 0.2 Co 0.2 Ni 0.2 Fe 0.2 )3O4, b perovskite La-(Mn 0.2 Cu 0.2 Co 0.2 Ni 0.2 Fe 0.2 )O3, c spinel (Ni 0.2 Mg 0.2 Cu 0.2 Mn 0.2 Co 0.2 )Al2O4 and d cubic phase Ni 0.2 Mg 0.2 Cu 0.2 Zn 0.2 Co 0.2 SEM image of O.

[0036] Figure 2 (Mg 0.4 Fe 0.2 Co 0.2 Ni 0.2 ) Stability data of Al2O4-co-melt for methane dry reforming at 750℃.

[0037] Figure 3 (Mg 0.4 Fe 0.2 Co 0.2 Ni 0.2 ) Stability data of Al2O4-Sol-Gel for methane dry reforming at 750℃.

[0038] Figure 4 (Mg 0.4 Ni 0.2 )Al2O 3.6 -co-melt methane dry reforming stability data at 750°C. DETAILED DESCRIPTION

[0039] The present invention will be further described in detail below in conjunction with the accompanying drawings.

[0040] Experimental equipment and materials: The required raw materials are various metal nitrates, anhydrous citric acid, etc.; the main instruments include scanning electron microscope (SEM), transmission electron microscope (TEM), X-ray diffractometer (XRD), etc.

[0041] Test conditions: Use a gas mixture flow rate of 30,000 mL g -1 cat -1 h -1 , containing 10mL min -1 CO2,10mL min -1 CH4, and 30 mL min -1 Ar was used to test the catalytic activity.

[0042] Analysis of results: Compared with samples prepared by the traditional sol-gel method, the nanosheets synthesized by the new method showed higher conversion rate and lower carbon deposition tendency, proving the importance of nanosheet morphology to catalytic performance.

[0043] Example 1: Ni 0.2 Mg 0.2 Cu 0.2 Zn 0.2 Co 0.2 Preparation of O

[0044] Raw material preparation: 3mmol each of magnesium, zinc, copper, cobalt and nickel nitrates, 22.5mmol of anhydrous citric acid. Mixing process: Add the above metal nitrates and citric acid into a beaker and shake manually to ensure initial uniform mixing.

[0045] Heating treatment: The mixture was placed in an oil bath and heated at 150°C with magnetic stirring until a foamy solid was formed.

[0046] Calcination process: The generated solid was placed in a muffle furnace and calcined at 1000°C in air for 5 hours.

[0047] Product characteristics: The target compound Ni is finally obtained 0.2 Mg 0.2 Cu 0.2 Zn 0.2 Co 0.2 OFlake materials.

[0048] Example 2: La-(Mn 0.2 Cu 0.2 Co 0.2 Ni 0.2 Fe 0.2 Preparation of )O3

[0049] Raw material preparation: 7 mmol of lanthanum nitrate, 1.4 mmol each of manganese, iron, cobalt and nickel nitrates, and 21 mmol of anhydrous citric acid.

[0050] Mixing process: same as in Example 1.

[0051] Heating treatment: Same as in Example 1, but the temperature was kept at 150°C.

[0052] Calcination process: Calcination at 700°C in air for 5 hours.

[0053] Product characteristics: The target compound La-(Mn 0.2 Cu 0.2 Co 0.2 Ni 0.2 Fe 0.2 )O3 flake material.

[0054] Embodiment 3: (Ni 0.2 Mg 0.2 Cu 0.2 Mn 0.2 Co 0.2 )Preparation of Al2O4

[0055] Raw material preparation: 2 mmol (magnesium, copper, cobalt, nickel) and 20 mmol (aluminum) nitrates of magnesium, copper, cobalt, nickel and aluminum respectively, 45 mmol (anhydrous citric acid).

[0056] Mixing process: same as in Example 1.

[0057] Heating treatment: Same as in Example 1, but the temperature was kept at 150°C.

[0058] Calcination process: Calcination at 700°C in air for 5 hours.

[0059] Product characteristics: The target compound (Ni 0.2 Mg 0.2 Cu 0.2 Mn 0.2 Co 0.2 )Al2O4 flake material.

[0060] Embodiment 4: (Cr 0.2 Mn 0.2 Co 0.2 Ni 0.2 Fe 0.2 Preparation of )3O4

[0061] Raw material preparation: 3 mmol each of chromium, manganese, iron, cobalt and nickel nitrates, 22.5 mmol of anhydrous citric acid.

[0062] Mixing process: same as in Example 1.

[0063] Heating treatment: Same as in Example 1, but the temperature was kept at 150°C.

[0064] Calcination process: Calcination at 700°C in air for 5 hours.

[0065] Product characteristics: The target compound (Cr 0.2 Mn 0.2 Co 0.2 Ni 0.2 Fe 0.2 )3O4 flake material.

[0066] Comparative Example 1: (Mg 0.4 Fe 0.2 Co 0.2 Ni 0.2 )Preparation of Al2O4-co-melt

[0067] Raw material preparation: nitrates of magnesium, iron, cobalt and nickel are 2, 1, 1, 1 mmol respectively, aluminum nitrate is 10 mmol, and anhydrous citric acid is 22.5 mmol.

[0068] Mixing process: same as in Example 1.

[0069] Heating treatment: Same as in Example 1, but the temperature was kept at 150°C.

[0070] Calcination process: Calcination at 700°C in air for 5 hours.

[0071] Product characteristics: The final product (Mg 0.4 Fe 0.2 Co 0.2 Ni 0.2 )Al2O4-co-melt compounds.

[0072] Comparative Example 2: (Mg 0.4 Fe 0.2 Co 0.2 Ni 0.2 )Preparation of Al2O4-Sol-Gel

[0073] Raw material preparation: nitrates of magnesium, iron, cobalt and nickel are 2, 1, 1, 1 mmol respectively, aluminum nitrate is 10 mmol, and anhydrous citric acid is 37.5 mmol.

[0074] Dissolution process: The above materials were dissolved in 40 mL of deionized water (CA:cations=2.5), heated to 40° C., and stirred continuously for 30 minutes.

[0075] Addition of EG: Ethylene glycol (EG / CA=1.5) was added to the solution and then the temperature was raised to 80°C until a gel was formed.

[0076] Drying process: Dry at 120℃ for 12 hours to evaporate the remaining moisture.

[0077] Pretreatment: 400°C in air.

[0078] Calcination process: Finally, calcination was carried out at 700°C for 12 hours in flowing air.

[0079] Product characteristics: The final product (Mg 0.4 Fe 0.2 Co 0.2 Ni 0.2 )Al2O4-Sol-Gel compound.

[0080] Comparative Example 3: (Mg 0.4 Ni 0.2 )Al2O 3.6 Preparation of -co-melt

[0081] Raw material preparation: 2.1 mmol of magnesium and nickel nitrates respectively, 10 mmol of aluminum nitrate, and 19.5 mmol of anhydrous citric acid.

[0082] Mixing process: same as in Example 1.

[0083] Heating treatment: Same as in Example 1, but the temperature was kept at 150°C.

[0084] Calcination process: Calcination at 700°C in air for 5 hours.

[0085] Product characteristics: The final product (Mg 0.4 Ni 0.2 )Al2O 3.6 -co-melt compounds.

[0086] Example 5

[0087] Use (Mg 0.4 Fe 0.2 Co 0.2 Ni 0.2 ) Al2O4-co-melt catalytic methane dry reforming to produce synthesis gas:

[0088] During the test, the catalyst dosage was 100 mg, and before dry reforming of methane, it was reduced with 10% H2 / 90% Ar (total flow rate was 50 STP mL / min) at 700°C for 2 h. Subsequently, Ar was purged for 10 min to replace the hydrogen in the system. After the replacement was completed, the temperature was raised to 750°C, and pure argon was switched to the reaction gas (10 ml CH4: 10 ml CO2: 30 ml Ar).

[0089] Example 6

[0090] Use (Mg 0.4 Fe 0.2 Co 0.2 Ni 0.2 ) Reaction of preparing synthesis gas by dry reforming of methane catalyzed by Al2O4-Sol-Gel:

[0091] During the test, the catalyst dosage was 100 mg, and before dry reforming of methane, it was reduced with 10% H2 / 90% Ar (total flow rate was 50 STP mL / min) at 700°C for 2 h. Subsequently, Ar was purged for 10 min to replace the hydrogen in the system. After the replacement was completed, the temperature was raised to 750°C, and pure argon was switched to the reaction gas (10 ml CH4: 10 ml CO2: 30 ml Ar).

[0092] Example 7

[0093] Use (Mg 0.4 Ni 0.2 )Al2O 3.6 -co-melt catalytic methane dry reforming to produce synthesis gas:

[0094] During the test, the catalyst dosage was 100 mg, and before dry reforming of methane, it was reduced with 10% H2 / 90% Ar (total flow rate was 50 STP mL / min) at 700°C for 2 h. Subsequently, Ar was purged for 10 min to replace the hydrogen in the system. After the replacement was completed, the temperature was raised to 750°C, and pure argon was switched to the reaction gas (10 ml CH4: 10 ml CO2: 30 ml Ar).

[0095] Figure 1 a is Ni 0.2 Mg 0.2 Cu 0.2 Zn 0.2 Co 0.2 SEM image of O; Figure 1 b is La-(Mn 0.2 Cu 0.2 Co 0.2 Ni 0.2 Fe 0.2 )SEM image of O3; Figure 1 b is (Ni 0.2 Mg 0.2 Cu 0.2 Mn 0.2 Co 0.2 )SEM image of Al2O4; Figure 1 b is (Cr 0.2 Mn 0.2 Co 0.2 Ni 0.2 Fe 0.2 )SEM image of 3O4.

[0096] All samples have a flaky structure, ranging in size from a few microns to hundreds of microns, and the lamellae are directly stacked, except for Ni 0.2 Mg 0.2 Cu 0.2 Zn 0.2 Co 0.2 Except for the relatively thick O layer, the single layer thickness of other materials ranges from a few nanometers to more than ten nanometers.

[0097] Figure 2 (Mg 0.4 Fe 0.2 Co 0.2 Ni 0.2 ) Stability data of Al2O4-co-melt for methane dry reforming at 750℃ for 400h, no significant decrease in CH4 conversion and CO2 conversion.

[0098] Figure 3 (Mg 0.4 Fe 0.2 Co 0.2 Ni 0.2) Stability data of Al2O4-Sol-Gel for methane dry reforming at 750℃ for 6h. The system was seriously blocked due to carbon deposition.

[0099] Figure 4 (Mg 0.4 Ni 0.2 )Al2O 3.6 -co-melt's 12h stability data for methane dry reforming at 750℃, the system was severely blocked by carbon deposition.

[0100] H2:CO(50h) graph, 50h 3Ni@SBA-15(700) had poor stability, and the methane conversion rate, carbon dioxide conversion rate, and H2:CO ratio showed a significant decrease.

Claims

1. A general method for synthesizing high entropy oxide nanosheets, characterized in that: The steps include: Step 1: premixing a plurality of hydrated metal nitrates and anhydrous citric acid in proportion to obtain a mixture; Step 2: heating the mixture in an oil bath and stirring it magnetically until a foamy substance is formed; Step 3: placing the foamed solid in a muffle furnace and calcining it in air to obtain high entropy oxide nanosheets after removing organic components.

2. A general synthesis method of high entropy oxide nanosheets according to claim 1, characterized in that: In the step 1, the ratio of the hydrated metal nitrate to anhydrous citric acid is 1-2.5 moles of anhydrous citric acid per mole of metal ion.

3. A general synthesis method of high entropy oxide nanosheets according to claim 1, characterized in that: In step 1, the hydrated metal nitrate is a mixture of any N elements that meet the solid solution properties among hydrated magnesium nitrate, hydrated cobalt nitrate, hydrated iron nitrate, hydrated nickel nitrate, hydrated aluminum nitrate, hydrated manganese nitrate, hydrated calcium nitrate, hydrated copper nitrate, and hydrated lanthanum nitrate, where N is greater than or equal to 5.

4. A general synthesis method of high entropy oxide nanosheets according to claim 1, characterized in that: In the step 2, the heating temperature in the oil bath is 120-150°C.

5. A general synthesis method of high entropy oxide nanosheets according to claim 1, characterized in that: In the step 3, calcination is performed at 500-1000° C. for 3-5 hours.

6. A general synthesis method of high entropy oxide nanosheets according to claim 1, characterized in that: The high entropy oxide nanosheets include but are not limited to the following structures: Inverse spinel (Cr 0.2 Mn 0.2 Co 0.2 Ni 0.2 Fe 0.2 )3O4、(Mg 0.4 Fe 0.2 Co 0.2 Ni 0.2 )Al2O4; Perovskite La-(Mn 0.2 Cu 0.2 Co 0.2 Ni 0.2 Fe 0.2 )O3; spinel (Ni 0.2 Mg 0.2 Cu 0.2 Mn 0.2 Co 0.2 )Al2O4; cubic Ni 0.2 Mg 0.2 Cu 0.2 Zn 0.2 Co 0.2 O.

7. A high entropy oxide nanosheet prepared by the method according to any one of claims 1 to 6, characterized in that: The high entropy oxide nanosheet is used as a catalyst in a methane dry reforming reaction.

8. The use according to claim 1, characterized in that: Specifically: The catalyst is subjected to 10% H2 and the rest Ar before the reaction, with Ar being the balance gas, and is reduced in situ at 700°C for 1-5h; then the catalyst is added to methane (CH4) and carbon dioxide (CO2) to react and generate synthesis gas, and the reaction is carried out at a temperature of 700-850°C and a reaction pressure of normal pressure; The feed gas ratio of CH4:CO2:Ar is 1:1:3 (Ar is the balance gas), and the space velocity GHSV is 30000 mL h - 1 gcat -1 .

9. Prepared by the method described in any one of claims 1 to 6 (Mg 0.4 Fe 0.2 Co 0.2 Ni 0.2 )Al2O4 high entropy oxide nanosheets, characterized in that The eutectic solvent-free method was used to synthesize (Mg 0.4 Fe 0.2 Co 0.2 Ni 0.2 )Al2O4-co-melt, (Mg 0.4 Fe 0.2 Co 0.2 Ni 0.2 )Al2O4 is spinel type.

10. (Mg according to claim 9 0.4 Fe 0.2 Co 0.2 Ni 0.2 )Al2O4 high entropy oxide nanosheets, characterized in that (Mg 0.4 Fe 0.2 Co 0.2 Ni 0.2 )Al2O4-co-melt presents a nanosheet structure rich in mesopores; (Mg 0.4 Fe 0.2 Co 0.2 Ni 0.2 )The metal elements in Al2O4-co-melt show high entropy characteristics of uniform dispersion. Among them, Fe, Co, and Ni elements can be reduced by H2 to form FeCoNi ternary alloys of uniform size and carried by nanosheets. The FeCoNi ternary alloy improves the electronic structure of Ni, making it more conducive to the adsorption and activation of methane and carbon dioxide.